Utility of clinical‐focused multiple mini interviews during postgraduate year one pharmacy residency interviews. Issue 4 (13th April 2020) - Austin Szwak, Jennifer; Bondi, Deborah S.; Knoebel, Randall; Soni, Hailey P.
Abstract: Introduction: Determining a candidate's clinical skills from an interview can be challenging with traditional interviewing techniques. Identifying techniques to objectively, reliably, and efficiently screen candidates is critical given the increasing number of postgraduate year one (PGY1) pharmacy residency applicants. Multiple mini interviews (MMIs) are one technique shown to correlate with clinical performance in the medical field; however, limited data exists for evaluating pharmacy residency candidates. Objectives: To determine if incorporating a clinical‐focused MMI would distinguish candidates who demonstrate stronger clinical skills during their PGY1 residency. Methods: This retrospective review compared the clinical MMI and traditional interview scores of all interviewed candidates from January 2015 to March 2017 and clinical performance of residents who matched at our institution. For candidates who matched at our institution, a clinical performance ranking (CPR) of each resident was determined by the PGY1 Residency Program Director based on a subjective rank of overall clinical skills. All candidates who matched at our institution had clinical MMI and traditional interview scores compared with the CPR using Pearson's correlation coefficients. Clinical MMI and traditional interview scores were also compared with the final rank list quartiles for all candidates with a one‐way ANOVA and Wilcoxon rank sum test, respectively. Results: For candidates matching at our institutions, clinical MMI scores strongly correlated with their CPR during the residency year ( R 2 = 0.7149), while traditional interview scores were very weak ( R 2 = 0.0818). Both clinical MMI and traditional interview scores of all candidates differed significantly between each quartile on the final rank list ( P < .05 for all comparisons). Conclusion: For residency candidates that matched at our institution, clinical MMI interview performance strongly correlated with CPR while traditional interview scores did not. Data from multiple centers is needed to better assess if clinical MMI scores can reliably predict a residency candidate's future clinical performance.